3040 How to write your first scholarly journal article using reporting guidelines as a template. (27th March 2019) - Selfe, Terry Kit
Abstract : OBJECTIVES/SPECIFIC AIMS: The objective of this session is to support and encourage novice, unpublished researchers to turn their poster content into a manuscript publishable in a scholarly journal, by showing them concrete steps to follow and research study reporting standards to use as a template. METHODS/STUDY POPULATION: We will cover the following topics: choosing a journal, finding the journal's requirements, locating the reporting standard for the study type (e.g., CONSORT for randomized trials), and structuring the manuscript appropriately per International Committee of Medical Journal Editors (ICMJE) recommendations (e.g., Introduction, Methods, Results, and Discussion). RESULTS/ANTICIPATED RESULTS: It is anticipated that by the end of the session, attendees should be able to: Select an appropriate journal; Organize a manuscript according to ICMJE guidelines; Compose a manuscript based on the applicable reporting standard (e.g. CONSORT). DISCUSSION/SIGNIFICANCE OF IMPACT: Providing novice researchers with information and resources that demystify the process of writing a manuscript suitable for a scholarly journal, is expected to bolster their confidence and increase the likelihood they will create and submit publishable manuscripts; thereby improving the dissemination of research findings and increasing research impact.